2019
DOI: 10.21474/ijar01/10047
|View full text |Cite
|
Sign up to set email alerts
|

Biodiversity, Distribution and Morphological Characterization of Macrofungi in Sylhet and Moulvibazar Under Tropical Evergreen and Semi - Evergreen Forest Regions of Bangladesh

Abstract: Tropical evergreen and semi-evergreen forest regions under Sylhet and Moulovibazar districts which is located at 24.8917°N and 91.8833°E, in the north eastern region of Bangladesh. A total of 53 macro fungal samples were collected and identified to 15 genera and 25 species. The predominant species were Ganoderma tsugae, Ganoderma applanatum, Ganoderma bonninese, Agaricus bernardii, Coprinus disseminates, Daeleopsis confragosa, Schizophyllum commune, Pleurotus ostreatus, Pleurotus populinus, Mycena epiptergia,S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 8 publications
1
12
0
Order By: Relevance
“…This species was found with the bark of Dalbergia sissoo (Sisso) under social forest region of Bangladesh [26]. Recently several species of Ganoderma was reported from tropical evergreen and semi-evergreen forest regions under Sylhet and Moulovibazar districts of Bangladesh [28]. Another study found this species on root of Terminalia bellirica (Bohera) [21].…”
Section: Ganoderma Resinaceum Was Found In Nationalmentioning
confidence: 99%
“…This species was found with the bark of Dalbergia sissoo (Sisso) under social forest region of Bangladesh [26]. Recently several species of Ganoderma was reported from tropical evergreen and semi-evergreen forest regions under Sylhet and Moulovibazar districts of Bangladesh [28]. Another study found this species on root of Terminalia bellirica (Bohera) [21].…”
Section: Ganoderma Resinaceum Was Found In Nationalmentioning
confidence: 99%
“…This genus was also reported from Southern region and tropical ever-green and semi-evergreen forest region of Bangladesh due to common climatic conditions. The average temperature is 12.1-35.1℃, average annual rainfall is 195 cm in Southern region and in Tropical ever-green and semi-evergreen forest region (Rashid et al, 2016;Tanjim et al, 2019). The average temperature is 12.1-35.1℃, average annual rainfall is 195 cm and average relative humidity is 70-84% of the collection site in the present study.…”
Section: Lingzhi Ormentioning
confidence: 50%
“…The pathogenicity of Ganoderma boninense was examined (Cooper et al, 2011). This species was also seen in Chittagong and Rangamati Hill Tracts as well as in Sylhet and Moulvibazar forest region (Tanjim et al, 2019). In tropical ever-green and semi-evergreen forest region, the average temperature is 12.1-35.1℃, average annual rainfall is 195 cm, average relative humidity is 70-84% recorded.…”
Section: Plate 1 Specimen Collected From Tropical Moist Deciduous Forest Regionmentioning
confidence: 69%
See 1 more Smart Citation
“…In other study Marzana et al (2018) found G. lucidum in Kaptai, Rangamati of Chittagong Hill tracts under tropical evergreen and semi-evergreen forest of Bangladesh. Tanjim et al, (2019) reported Ganoderma species in tropical evergreen and semi-evergreen forest region of Bangladesh and Tanni et al, (2020) also reported the species from forest tree of different parks and gardens of Dhaka city, Bangladesh.…”
Section: Discussionmentioning
confidence: 99%